Introduction of practical classes in science teaching in a public institution in the state of Sergipe/Brazil (Research, Society and Development, 2022)
The present work has the purpose of analyzing the importance of the use of active methodologies in the construction of knowledge of science in elementary education under the perspective of the development of competences and skills. Therefore, Science Education is very important because it addresses general scientific principles and, also, technological applications. Scientific concepts and theories do not have values in themselves, as abstract systems of thought, but as instruments that help us to understand the world in which we live in order to guide our actions at the individual and social level. The practice linked to theory makes a lot of difference for a contextualized class, where students can see the importance of the contents addressed in the teaching of science, in addition to offering them greater clarity so that they can really interpret or be part of the study in question. . It is visible today the need for experimentation during classes as a teaching tool, because the stimulus and interest of students becomes much greater, since they can visualize the content in a different way, that is, they can analyze certain issues as if they were part of it. Therefore, the experimental practice has a broader role than expected, because it develops in the students a greater interest, besides awakening skills that did not appear in the theoretical classes, for example.